2016
DOI: 10.1631/jzus.b1600052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tai Chi exercise on blood lipid profiles: a meta-analysis of randomized controlled trials

Abstract: Abstract:Objective: Studies have demonstrated that Tai Chi exercise improves blood lipid level with inconsistent results. A meta-analysis was conducted to quantify the effects of Tai Chi on blood lipid profiles in humans. Methods: We screened the databases of PubMed, EMBASE, Cochrane Library (Central), Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang data, and Clinicaltrials.gov for randomized controlled trials with Physiotherapy Evidence Database (PEDro) score more than 3 points up to J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
(85 reference statements)
3
23
0
Order By: Relevance
“…However, in the present study, no statistically significant differences were observed in the biochemical markers mentioned above. In this sense, Pan et al 41 reported in a meta-analysis of randomized controlled trials a statistically significant decrease in blood triglyceride concentration but found no statistically significant differences in total cholesterol, LDL-C, and HDL-C concentrations. Other studies support the proposal that there are no changes in parameters related to metabolic syndrome such as dyslipidemias, hyperglycemia, and waist circumference after TC training.…”
Section: Discussionmentioning
confidence: 98%
“…However, in the present study, no statistically significant differences were observed in the biochemical markers mentioned above. In this sense, Pan et al 41 reported in a meta-analysis of randomized controlled trials a statistically significant decrease in blood triglyceride concentration but found no statistically significant differences in total cholesterol, LDL-C, and HDL-C concentrations. Other studies support the proposal that there are no changes in parameters related to metabolic syndrome such as dyslipidemias, hyperglycemia, and waist circumference after TC training.…”
Section: Discussionmentioning
confidence: 98%
“…By means of regulating ion channels [ 7 , 8 , 22 , 33 , 37 , 38 , 41 , 54 ], they act positive roles in rhythm or rate control. They also give a hand to the risk factors by vasodilation [ 7 ], anti-inflammatory effect [ 9 , 19 ], antioxidant activity [ 10 , 30 , 72 ], and even resistance of myocardium remodeling [ 50 , 71 ] and benefit some primary diseases such as heart failure [ 7 , 26 , 41 ], hypertension [ 27 , 69 ], and dyslipidemia [ 70 , 76 ]. In addition, antiplatelet aggregation [ 12 , 34 , 39 ] and fibrinolysis effect [ 39 ] are showed in some CHMs or bioactive ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent research further indicated its efficacy in the improvement of cardiorespiratory function for old adults [ 74 ]. And a meta-analysis demonstrated that TCC lowered blood triglyceride level with a trend to decrease blood total cholesterol level [ 76 ]. What is more, as an aerobic exercise of moderate intensity, TCC could maintain better health and improve quality of life, thus reducing CVD risk factors [ 75 ].…”
Section: Nondrug Methodsmentioning
confidence: 99%
“…For instance, Qigong exercise enhanced balance and fitness as well as somatosensation in diabetes mellitus patients (Cavegn and Riskowski, 2015), decreased fatigue, improved sleep quality along with increased white blood cell counts and hemoglobin levels in non-Hodgkin lymphoma patients (Chuang et al, 2017). Moreover, practicing such exercises may also impact on lipid metabolism, but information on most appropriate intensity and duration is still lacking (Pan et al, 2016). Endurance exercise is associated with enhanced oxygen consumption also resulting in elevated production of reactive oxygen species (ROS) (Alessio, 1993).…”
Section: Introductionmentioning
confidence: 99%